A RESPONSE TO LOKE'S 'IS AN INFINITE TEMPORAL REGRESS OF EVENTS POSSIBLE?' (THINK 31). Issue 36 (17th December 2013) - Lyth, Peter
<x content-type="archive" xml:space="preserve">Abstract</x> Loke argues against the possibility of any infinite collection, mainly on the grounds that number as an abstract entity (if it exists) cannot have causal power. But I argue that his argument conflates number as an abstract entity with number as a number of events or things. Loke also maintains that a situation of 'infinities upon infinities' poses problems, and I argue against this. Finally, Loke queries how an 'extra' can be added to an infinite collection, but I suggest this is here a misleading word.